A new species of Bent-toed gecko (Squamata: Gekkonidae: Cyrtodactylus Gray, 1827) from the Garo Hills, Meghalaya State, north-east India, and discussion of morphological variation for C. urbanus. Issue 3 (July 2021) - , Rachunliu G. Kamei; Mahony, Stephen
No abstract available